Branding Argowisata Kebun Melon Sumber Berkah Balikpapan melalui Media Sosial dan Fasilitas Penunjang - Putri, Hesti Rosita Dwi; Hijriah, Hijriah; Permana, Riyan Hadi; Baransano, Hendri; Nababan, Narumi Patricia; Firdausi, Abidzar Cahyana; Florentin, Siahaan Lita Sinta; Aisy, Afifah Raidatul; Nurhalisa, Nurhalisa; Salsabila, Salsabila (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2024)
Balikpapan City has the potential for argotourism, namely Kebun Melon Sumber Berkah, in addition to agriculture as well as educational tourism such as providing planting and harvesting experiences. Educational activities carried out become brand positioning so that Kebun Melon Sumber Berkah is more easily recognised by the public. Promotional activities carried out have not displayed in accordance with the identity of Kebun Melon Sumber Berkah, besides that supporting facilities to support Kebun Melon Sumber Berkah as argotourism are still very minimal. Based on this, the purpose of this activity is to strengthen the image or position as argotourism and maximise its educational potential. The method used is ABCD or Asset Based Community Development which is carried out with 4 stages, namely preparation, implementation, analysis and utilisation of results. The result of this activity is that visitors are satisfied with the programme carried out so that the promotion and facilities of Kebun Melon Sumber Berkah are easily known as educational tourism.